The Overexpression of Collagen Receptor DDR1 is Associated With Chromosome Instability and Aneuploidy in Diffuse Large B-Cell Lymphoma - Margielewska-Davies, Sandra; Pugh, Matthew; Nagy, Eszter; Leahy, Ciara I; Ibrahim, Maha; Fennell, Eanna; Ross, Aisling; Bouchal, Jan; Lupino, Lauren; Care, Matthew; Tooze, Reuben; Reynolds, Gary; et al. (Journal of cellular and molecular medicine, 2025)
Although chronic inflammation is implicated in the pathogenesis of diffuse large B-cell lymphoma (DLBCL), the mechanisms responsible are unknown. We demonstrate that the overexpression of the collagen receptor, DDR1, correlates with reduced expression of spindle checkpoint genes, with three transcriptional signatures of aneuploidy and with a higher frequency of copy number alterations, pointing to a potential role for DDR1 in the acquisition of aneuploidy in DLBCL. In support of this, we found that collagen treatment of primary germinal centre B cells transduced with DDR1, not only partially recapitulated the aberrant transcriptional programme of DLBCL but also downregulated the expression of CENPE, a mitotic spindle that has a crucial role in preventing chromosome mis-segregation. CENPE expression was also downregulated following DDR1 activation in two B-cell lymphoma lines and was lost in most DDR1-expressing primary tumours. Crucially, the inhibition of CENPE and the overexpression of a constitutively activated DDR1 were able to induce aneuploidy in vitro. Our findings identify a novel mechanistic link between DDR1 signalling and chromosome instability in B cells and provide novel insights into factors driving aneuploidy in DLBCL.
Keywords: Gene Expression Regulation, Neoplastic; TP53; chromozomální nestabilita; Chromosomal Instability; Discoidin Domain Receptor 1; Cell Line, Tumor; DLBCL; Lymphoma, Large B-Cell, Diffuse; regulace genové exprese u nádorů; signální transdukce; B-lymfocyty; mitotic spindle; kolagen; receptor DDR1; Signal Transduction; aneuploidy; collagen; DDR1; aneuploidie; lidé; difúzní velkobuněčný B-lymfom; Aneuploidy; Humans; Collagen; chromosome instability; B-Lymphocytes; nádorové buněčné linie; CENPE